Discover the answers you need at Westonci.ca, where experts provide clear and concise information on various topics. Experience the ease of finding reliable answers to your questions from a vast community of knowledgeable experts. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
To solve the given system of equations:
[tex]\[ \begin{cases} 2x + 7y = -7 \\ -4x - 3y = -19 \end{cases} \][/tex]
we need to find the values of [tex]\( x \)[/tex] and [tex]\( y \)[/tex] that simultaneously satisfy both equations. Here’s a detailed step-by-step process:
1. Label the equations:
[tex]\[ \begin{aligned} &\text{(1)} \quad 2x + 7y = -7 \\ &\text{(2)} \quad -4x - 3y = -19 \end{aligned} \][/tex]
2. Multiply the equations to align coefficients for elimination:
We'll multiply the first equation by 2 to match the coefficients of [tex]\( x \)[/tex] in magnitude with that in the second equation:
[tex]\[ 2 \times (2x + 7y) = 2 \times (-7) \][/tex]
This gives us:
[tex]\[ 4x + 14y = -14 \quad \text{(3)} \][/tex]
3. Add equation (3) to equation (2):
[tex]\[ (4x + 14y) + (-4x - 3y) = -14 + (-19) \][/tex]
Simplify the left and right sides:
[tex]\[ (4x - 4x) + (14y - 3y) = -14 - 19 \][/tex]
This simplifies to:
[tex]\[ 11y = -33 \][/tex]
4. Solve for [tex]\( y \)[/tex]:
[tex]\[ y = \frac{-33}{11} = -3 \][/tex]
5. Substitute [tex]\( y = -3 \)[/tex] back into equation (1) to find [tex]\( x \)[/tex]:
[tex]\[ 2x + 7(-3) = -7 \][/tex]
Simplify:
[tex]\[ 2x - 21 = -7 \][/tex]
Add 21 to both sides:
[tex]\[ 2x = 14 \][/tex]
Divide by 2:
[tex]\[ x = 7 \][/tex]
The solution to the system of equations is [tex]\( x = 7 \)[/tex] and [tex]\( y = -3 \)[/tex]. Expressed as an ordered pair, the solution is:
[tex]\[ (7,-3) \][/tex]
[tex]\[ \begin{cases} 2x + 7y = -7 \\ -4x - 3y = -19 \end{cases} \][/tex]
we need to find the values of [tex]\( x \)[/tex] and [tex]\( y \)[/tex] that simultaneously satisfy both equations. Here’s a detailed step-by-step process:
1. Label the equations:
[tex]\[ \begin{aligned} &\text{(1)} \quad 2x + 7y = -7 \\ &\text{(2)} \quad -4x - 3y = -19 \end{aligned} \][/tex]
2. Multiply the equations to align coefficients for elimination:
We'll multiply the first equation by 2 to match the coefficients of [tex]\( x \)[/tex] in magnitude with that in the second equation:
[tex]\[ 2 \times (2x + 7y) = 2 \times (-7) \][/tex]
This gives us:
[tex]\[ 4x + 14y = -14 \quad \text{(3)} \][/tex]
3. Add equation (3) to equation (2):
[tex]\[ (4x + 14y) + (-4x - 3y) = -14 + (-19) \][/tex]
Simplify the left and right sides:
[tex]\[ (4x - 4x) + (14y - 3y) = -14 - 19 \][/tex]
This simplifies to:
[tex]\[ 11y = -33 \][/tex]
4. Solve for [tex]\( y \)[/tex]:
[tex]\[ y = \frac{-33}{11} = -3 \][/tex]
5. Substitute [tex]\( y = -3 \)[/tex] back into equation (1) to find [tex]\( x \)[/tex]:
[tex]\[ 2x + 7(-3) = -7 \][/tex]
Simplify:
[tex]\[ 2x - 21 = -7 \][/tex]
Add 21 to both sides:
[tex]\[ 2x = 14 \][/tex]
Divide by 2:
[tex]\[ x = 7 \][/tex]
The solution to the system of equations is [tex]\( x = 7 \)[/tex] and [tex]\( y = -3 \)[/tex]. Expressed as an ordered pair, the solution is:
[tex]\[ (7,-3) \][/tex]
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.